European Academy of Andrology guideline Management of oligo‐astheno‐teratozoospermia. (1st August 2018) - Colpi, G. M.; Francavilla, S.; Haidl, G.; Link, K.; Behre, H. M.; Goulis, D. G.; Krausz, C.; Giwercman, A.
Summary: Background: Oligo‐astheno‐teratozoospermia is frequently reported in men from infertile couples. Its etiology remains, in the majority of cases, unknown with a variety of factors to contribute to its pathogenesis. The aim of this European Academy of Andrology guideline was to provide an overview of these factors and to discuss available management options. Materials and Methods: PubMed was searched for papers in English for articles with search terms: male infertility and oligo‐astheno‐teratozoospermia. For evidence‐based recommendations, the GRADE system was applied. Issues related to urogenital infections/inflammations have not been included in this document as they will be covered by separate guidelines. Results: For men with oligo‐astheno‐teratozoospermia, the European Academy of Andrology recommends: A general physical examination to assess signs of hypogonadism. A scrotal physical examination to assess (i) the testes and epididymes for volume and consistency, (ii) deferent ducts for total or partial absence, and (iii) occurrence of varicocoele. Performing two semen analyses, according to World Health Organization guidelines to define an oligo‐astheno‐teratozoospermia. An endocrine evaluation. A scrotal ultrasound as part of routine investigation. Karyotype analysis and assessment of Yq microdeletions in infertile men with a sperm concentration ≤5 × 10 6 /mL. Cystic fibrosis transmembrane conductance regulator gene evaluation in case of suspicion for incomplete congenital obstruction of the genital tract. Against quitting physical activity to improve the chance of achieving pregnancy. Against androgen replacement therapy to improve the chance of achieving pregnancy. Assisted reproduction techniques to improve the chance of achieving pregnancy, in case other treatment options are not available or not efficient. Androgen replacement therapy in patients with biochemical/clinical signs of hypogonadism, after completion of the fertility treatment. Conclusion: These guidelines can be applied in clinical work and indicate future research needs.